PELATIHAN PEMANFAATAN APLIKASI RUMAH BELAJAR UNTUK MEMBANTU PEMBELAJARAN PADA MASA PANDEMI BAGI GURU-GURU DI YAYASAN WALADUN SHOLEH - Veri Julianto; Arif Supriyanto; Yunita Prastyaningsih; Wan Yuliyanti (Jurnal WIDYA LAKSMI (Jurnal Pengabdian Kepada Masyarakat), 2022)
Learning that takes place at the Waladun Sholeh school is carried out online by utilizing several learning platforms, but there are some educators/teachers who are still lacking in literacy in the utilization and use of learning platforms, one of which is the Learning House portal. Therefore, it is necessary to train in the use of learning houses for learning during the pandemic for educators/teachers. Training on the use of learning houses for learning during the pandemic was carried out as a solution to the problem of lack of literacy in the use and utilization of learning portals. This training was wrapped in the form of community service and was held on December 17, 2021 at the Bill Gates Computer Laboratory, Department of Informatics, which was attended by 20 school teachers, Waladun Sholeh. The training provided is registration materials in the study house, uploading and downloading materials at the study house. As a result, 97.65% of participants stated that they were very satisfied with the training provided.